Reducing serious fall-related injuries in acute hospitals: Are low-low beds a critical success factor? - Barker, A.; Kamar, J.; Tyndall, T.; Hill, Keith (Blackwell Publishing Ltd, 2012)
Aim: This article is a report of a study of associations between occurrence of serious fall-related injuries and implementation of low-low beds at The Northern Hospital, Victoria, Australia. Background: A 9-year evaluation at The Northern Hospital found an important reduction in fall-related injuries after the 6-PACK falls prevention program was implemented. Low-low beds are a key component of the 6-PACK that aims to decrease fall-related injuries. Design: A retrospective cohort study. Methods: Retrospective audit of The Northern Hospital inpatients admitted between 1999–2009. Changes in serious fall-related injuries throughout the period and associations with available low-low beds were analysed using Poisson regression. Results: During the observation of 356,158 inpatients, there were 3946 falls and 1005 fall-related injuries of which 60 (5.9%) were serious (55 fractures and five subdural haematomas). Serious fall-related injuries declined significantly throughout the period. When there was one low-low bed to nine or more standard beds there was no statistically significant decrease in serious fall-related injuries. An important reduction only occurred when there was one low-low bed to three standard beds. Conclusion: The 6-PACK program has been in place since 2002 at The Northern Hospital. Throughout this time serious fall-related injuries have decreased. There appears to be an association between serious fall-related injuries and the number of available low-low beds. Threshold numbers of these beds may be required to achieve optimal usability and effectiveness. A randomized controlled trial is required to give additional evidence for use of low-low beds for injury prevention in hospitals.